2007
DOI: 10.1111/j.1440-0960.2007.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Facial Sweet’s syndrome mimicking rosacea fulminans

Abstract: A 36-year-old man presented with a non-pruritic, erythematous facial rash with peri-oral and peri-orbital sparing. The initial clinicopathological diagnosis was rosacea fulminans, which was treated with 25 mg oral prednisolone and cephalexin. The patient re-presented 1 week later with exacerbation of his rash in addition to constitutional symptoms of fever and malaise. A further skin biopsy was taken and the marked neutrophilic infiltrate in the absence of vasculitis made the diagnosis of Sweet's syndrome (acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
(4 reference statements)
0
10
0
1
Order By: Relevance
“…These disorders consist of not only cutaneous conditions and systemic diseases, but also infectious and inflammatory disorders, neoplastic conditions, reactive erythemas, and vasculitis (Figure 10). The clinical differential diagnosis of Sweet's syndrome is listed in Table 8[2,15,23,148,165,194,202,220,344,345,400,412,422]. …”
Section: Differential Diagnosismentioning
confidence: 99%
“…These disorders consist of not only cutaneous conditions and systemic diseases, but also infectious and inflammatory disorders, neoplastic conditions, reactive erythemas, and vasculitis (Figure 10). The clinical differential diagnosis of Sweet's syndrome is listed in Table 8[2,15,23,148,165,194,202,220,344,345,400,412,422]. …”
Section: Differential Diagnosismentioning
confidence: 99%
“…They were able to get rapid clinical improvement by high dose oral prednisolone, topical hydrocortisone cream and ichthamol in Zn ointment [152]. This study showed thattopical Zn may be effective in treating the manifestations of Sweet's syndrome via regulation of neutrophils.…”
Section: Sweet's Syndromementioning
confidence: 71%
“…Sweet's syndrome Characterized by nodular and diffuse dermal infiltrate of neutrophils along with karyorrhexis and papillary dermal edema [139] Unknown [152] Topical Zn preparation may be effective in treating this disease [152].…”
Section: ] Unknownmentioning
confidence: 99%
“…These findings therefore strongly indicate an important role of UV irradiation in the induction of Sweet's syndrome in our patient. UV-induced Sweet's syndrome is a rare condition, which has been reported to mimic photoallergic contact dermatitis or rosacea (6,7). In one report Sweet's syndrome was inducible by UVAl, but not UVB phototesting, and the lesions developed after 4 days (8).…”
Section: Discussionmentioning
confidence: 99%